Nitrate Reductase Complex of Escherichia coli K-12: Participation of Specific Formate Dehydrogenase and Cytochrome b(1) Components in Nitrate Reduction - Ruiz-Herrera, José (1969)
The participation of distinct formate dehydrogenases and cytochrome components in nitrate reduction by Escherichia coli was studied. The formate dehydrogenase activity present in extracts prepared from nitrate-induced cells of strain HfrH was active with various electron acceptors, including methylene blue, phenazine methosulfate, and benzyl viologen. Certain mutants which are unable to reduce nitrate had low or undetectable levels of formate dehydrogenase activity assayed with methylene blue or phenazine methosulfate as electron acceptor. Of nine such mutants, five produced gas when grown anaerobically without nitrate and possessed a benzyl viologen-linked formate dehydrogenase activity, suggesting that distinct formate dehydrogenases participate in the nitrate reductase and formic hydrogenlyase systems. The other four mutants formed little gas when grown anaerobically in the absence of nitrate and lacked the benzyl viologen-linked formate dehydrogenase as well as the methylene blue or phenazine methosulfate-linked activity. The cytochrome b(1) present in nitrate-induced cells was distinguished by its spectral properties and its genetic control from the major cytochrome b(1) components of aerobic cells and of cells grown anaerobically in the absence of nitrate. The nitrate-specific cytochrome b(1) was completely and rapidly reduced by 1 mm formate but was not reduced by 1 mm reduced nicotinamide adenine dinucleotide; ascorbate reduced only part of the cytochrome b(1) which was reduced by formate. When nitrate was added, the formate-reduced cytochrome b(1) was oxidized with biphasic kinetics, but the ascorbate-reduced cytochrome b(1) was oxidized with monophasic kinetics. The inhibitory effects of n-heptyl hydroxyquinoline-N-oxide on the oxidation of cytochrome b(1) by nitrate provided evidence that the nitrate-specific cytochrome is composed of two components which have different redox potentials but identical spectral properties. We conclude from these studies that nitrate reduction in E. coli is mediated by the sequential operation of a specific formate dehydrogenase, two specific cytochrome b(1) components, and nitrate reductase.